Power converters as natural gyrators - Ehsani, Mehrdad; Husain, Iqbal; Bilgiç, Mehmet Oruç (IEEE, 1993)
The authors investigate the open-loop gyrator behavior of a class of DC-DC converters that are characterized by double bridges. If the switching frequency of the double bridge converter is high enough with respect to its natural frequencies, the converter can be viewed as a gyrator from its terminals. Unlike other gyrator modeling approaches for converters, the double bridge converters naturally behave as gyrators without any extra control circuits.
Keywords: Gyrators; Bridge circuits; Switching converters; Force control; DC-DC power converters; Equations; Circuit topology; Switches; Associative memory; Neural networks